2014
DOI: 10.1152/ajpcell.00205.2013
|View full text |Cite
|
Sign up to set email alerts
|

Induced overexpression of OCT4A in human embryonic stem cells increases cloning efficiency

Abstract: Our knowledge of the molecular mechanisms underlying human embryonic stem cell (hESC) selfrenewal and differentiation is incomplete. The level of octamerbinding transcription factor 4 (Oct4), a critical regulator of pluripotency, is precisely controlled in mouse embryonic stem cells. However, studies of human OCT4 are often confounded by the presence of three isoforms and six expressed pseudogenes, which has complicated the interpretation of results. Using an inducible lentiviral overexpression and knockdown s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Alternative splicing of the POU5F1 primary transcript generates five transcript variants, encoding the isoforms OCT4A, OCT4B-190, OCT4B-265, OCT4B-164 and OCT4B1 [1517]. OCT4A is the most studied and described isoform, originally reported as a regulator of ESC pluripotency and self-renewal [18], while OCT4B and OCT4B1 functions are still uncertain. There are reports of OCT4B and OCT4B1 involvement with genotoxic stress and anti-apoptotic properties [16,19], but no clear association with stemness [20].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing of the POU5F1 primary transcript generates five transcript variants, encoding the isoforms OCT4A, OCT4B-190, OCT4B-265, OCT4B-164 and OCT4B1 [1517]. OCT4A is the most studied and described isoform, originally reported as a regulator of ESC pluripotency and self-renewal [18], while OCT4B and OCT4B1 functions are still uncertain. There are reports of OCT4B and OCT4B1 involvement with genotoxic stress and anti-apoptotic properties [16,19], but no clear association with stemness [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, studies have been reported on the regulation of AS during differentiation and reprogramming of mouse and human ESCs (Pritsker et al, 2005; Sugnet et al, 2006; Yeo et al, 2007; Kunarso et al, 2008; Salomonis et al, 2009; Salomonis et al, 2010; Wu et al, 2010; Gabut et al, 2011; Ohta et al, 2013b). Pluripotency-associated transcripts such as Dnmt3b, Nanog, Sall4 , and Oct4 have been shown to be themselves subjected to AS (Atlasi et al, 2008; Gopalakrishnan et al, 2009; Rao et al, 2010; Das et al, 2011; Tsai et al, 2014). The importance of the regulation of alternative splicing for the maintenance of the stem cell state and differentiation is exemplified by stage-specific splicing factors such as Rbfox2, Mbnl1, and Son in the pluripotency control process.…”
Section: Functions Of Rbps In Esc Maintenance Differentiation and Rmentioning
confidence: 99%
“…Another Oct4 splicing regulator in hESCs is Tip110, which regulates the Oct4A splicing variant both in vitro and in vivo, and is necessary for hESC maintenance (Liu et al, 2012; Liu et al, 2013). Oct4A has been shown to be the Oct4 variant responsible for maintenance of pluripotency (Tsai et al, 2014). Son and Tip110 regulate AS of pluripotency transcripts in a gene specific manner.…”
Section: Functions Of Rbps In Esc Maintenance Differentiation and Rmentioning
confidence: 99%
“…There may be many reasons for the lack of FGF5 detection in previous studies, but, at the very least, the results presented by Tsai et al (8) suggest that the OCT4A knockdown cells may pass through an FGF5-positive "epiblast-like" stage during differentiation. There may be many reasons for the lack of FGF5 detection in previous studies, but, at the very least, the results presented by Tsai et al (8) suggest that the OCT4A knockdown cells may pass through an FGF5-positive "epiblast-like" stage during differentiation.…”
mentioning
confidence: 98%